Strengthening Law Enforcement and Public Awareness to Combat Human Trafficking in Indonesia: Challenges and Solutions - Saffanah, Thariani; Rasito, Rasito; Putra, DI Ansusa; Yuliatin, Yuliatin (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Human trafficking remains a significant human rights issue in Indonesia, despite the nation’s comprehensive legal framework aimed at preventing crime and upholding justice. This pervasive problem predominantly targets women and children, exploiting their vulnerability through forced labor, sexual exploitation, and slavery. The increasing prevalence of human trafficking highlights gaps in law enforcement, insufficient government commitment, and limited societal awareness, making it urgent to strengthen preventive measures and legal implementation. This study seeks to analyze the challenges in combating human trafficking while exploring strategies to enhance law enforcement and public participation. Employing a qualitative approach, the research utilizes library-based methods with data collected through document analysis, focusing on Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. The findings reveal significant shortcomings in legal enforcement due to inadequate budget allocation, poor coordination among stakeholders, and the lack of robust community education. Despite the legal framework’s potential, the government’s efforts in ensuring security, developing infrastructure, and addressing societal awareness remain insufficient. The study emphasizes the need for harmonized regulations, increased resource allocation, and cultural and gender-sensitive approaches to strengthen protection and rehabilitation initiatives. By fostering public awareness, regular program evaluation, and collaborative reforms, Indonesia can address the systemic challenges and adopt a holistic strategy to combat human trafficking effectively, ensuring justice for victims and preventing further exploitation.